High Speed Non-Linear Circuit Simulation of Bipolar Junction Transistors. (1999) - Doja, M. N.; Moinuddin,; Kumar, Umesh
Abstract : This paper presents HIBTRA (High Speed Bipolar Transistor Analysis), a high speed non-linear bipolar transistor circuit simulation package. The paper discusses about the modelling of Bipolar Junction Transistor operated at high speed in the sinusoidal small signal and the transient region of operations. The package uses a high frequency model non-linear circuit elements for accurate analysis. The package also uses transistor's lumped circuit model to calculate devices electrical parameters, and it also does dynamic simulation. It also includes the conventional model as a special case. Model verification has also been done by simulation.